The Influence of Satellite Trails on H.E.S.S. Gamma-Ray Astronomical Observations - Spencer, Samuel; Lang, Thomas; Mitchell, Alison (38th International Cosmic Ray Conference (ICRC2023), 2023)
The number of satellites launched into low earth orbit has almost tripled (to over 4000) in the last three years due to the increasing commercialisation of space. Satellite constellations with a total of over 400,000 satellites are proposed to be launched in the near future. Many of these satellites are highly reflective, resulting in a high optical brightness that affects ground-based astronomical observations across the electromagnetic spectrum. Despite this, the potential effect of these satellites on Imaging Atmospheric Cherenkov Telescopes (IACTs) has so far been assumed to be negligible due to their nanosecond integration times. This has, however, never been verified. We aim to identify satellite trails in data taken by the High Energy Stereoscopic System (H.E.S.S.) IACT array in Namibia, using Night Sky Background (NSB) data from the CT5 camera installed in 2019. We determine which observation times and pointing directions are affected the most, and evaluate the impact on Hillas parameters used for classification and reconstruction of high-energy Extensive Air Shower events. Finally, we predict how future planned satellite launches will affect gamma-ray observations with IACTs.<br